SENI GERAK TARI ANAK USIA DINI - Amirah Syarifah Sirait; Hilda Zahra Lubis; Najwa Mahfuza; Ainin Ditya; Mutiara Alya; Putri Puspita Hasri (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to comprehensively examine teachers' strategies in integrating movement and dance arts learning for early childhood at RA Darul Madani. The research employed a qualitative descriptive method, utilizing observation, interviews, and documentation for data collection. The findings indicate that teachers at RA Darul Madani implement various creative strategies, such as using music and teaching aids, selecting age-appropriate and simple movements, and creating an enjoyable learning atmosphere. Movement and dance arts learning is integrated with other subjects, such as introducing numbers, letters, and character values. The main supporting factors for successful learning include school facilities and children's enthusiasm, while the obstacles encountered involve limited time, resources, and teachers' competence in the arts. Overall, movement and dance arts learning at RA Darul Madani positively impacts the motor, cognitive, social, and emotional development of early childhood students. The study recommends enhancing teacher training and providing supporting facilities to optimize arts learning.